Pengaruh Latar Belakang Negara Asal Terhadap Produk Asing Di Pasar Global - Nurwisesa; Sayed Haikal Fuad (CV. KAMPUS AKADEMIK PUBLISING, 2023)
This research investigates how country of origin background affects foreign products in the global market. In the current era of globalization, international and multinational markets are expanding rapidly, resulting in greater sales of foreign products around the world. Brand is one of the identities of a foreign product that can be easily recognized by consumers, and often potential buyers believe that a certain brand is associated with a certain country, which may affect their perception of product quality. According to some journals, country of origin or country of origin is a mental bond and belief created by a country. Consumers' perception of a product's country of origin can influence their decision-making directly or indirectly. As a result, it is crucial to understand the term